Investigating the Role of Traditional Foods in Promoting Nutritional Well-Being Among Rural Populations - Nurhayati, Ai (International Journal of Engineering, Science and Information Technology, 2025)
Traditional foods play a crucial role in maintaining nutritional well-being, especially among rural homemakers responsible for household food management. This study examines the socio-cultural, economic, policy, and technological factors influencing traditional food consumption in rural Bandung. A mixed-methods approach was employed, combining quantitative surveys (n=150) and qualitative interviews (n=30) to assess household food consumption patterns, economic accessibility, and awareness of traditional food benefits. Statistical analyses, including Chi-Square tests and ANOVA, were used to evaluate the relationship between income levels and traditional food consumption behaviour. The findings indicate that low-income households rely more on conventional foods due to affordability, while higher-income groups consume them less frequently despite greater nutritional awareness. Additionally, modernization and urbanization have declined traditional food consumption as processed foods become more accessible. Government interventions, such as food subsidies, school nutrition programs, and traditional food certifications, have been identified as key factors in sustaining traditional food systems. Furthermore, digital technology and e-commerce offer new opportunities for small-scale traditional food producers to expand their market reach. However, challenges such as limited digital literacy and market competition require targeted interventions. This study underscores the importance of integrating policy support, education, and digital innovation to preserve traditional foods. Ensuring their sustainability will require collaborative efforts between governments, communities, and the private sector. By doing so, traditional foods can continue contributing to food security, cultural identity, and public health in Indonesia's rural communities.